2021
DOI: 10.21203/rs.3.rs-1034007/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Barriers and enablers to pulmonary rehabilitation in low- and middle-income countries: a qualitative study of healthcare professionals

Abstract: Low- and middle-income countries bear a disproportionately high burden of global morbidity and mortality caused by chronic respiratory diseases. Pulmonary rehabilitation is recommended as a core intervention in the management of people with chronic respiratory diseases. However, the intervention remains poorly accessed/utilised globally, especially in low- and middle-income countries. This qualitative study explored barriers and enablers to pulmonary rehabilitation in low- and middle-income countries from the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…A global audit of cardiac rehabilitation programs revealed that in only 40% of LMIC such rehabilitation services are available; roughly translating to one cardiac rehabilitation spot available for every 66 patients with ischaemic heart disease. (6,8) However, this gap in the availability of cardiac rehabilitation specifically, is illustrative for a broader need for rehabilitation type services in general, including rehabilitation for lung health, (10) access to assistive technology, (11) cardiometabolic disease, and others. (12,13) To address these needs, a concerted effort is needed to scale-up access to rehabilitation services (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…A global audit of cardiac rehabilitation programs revealed that in only 40% of LMIC such rehabilitation services are available; roughly translating to one cardiac rehabilitation spot available for every 66 patients with ischaemic heart disease. (6,8) However, this gap in the availability of cardiac rehabilitation specifically, is illustrative for a broader need for rehabilitation type services in general, including rehabilitation for lung health, (10) access to assistive technology, (11) cardiometabolic disease, and others. (12,13) To address these needs, a concerted effort is needed to scale-up access to rehabilitation services (Figure 1).…”
Section: Introductionmentioning
confidence: 99%